1980
DOI: 10.1007/bf01983542
|View full text |Cite
|
Sign up to set email alerts
|

Zur Determination der zeitlichen Verteilung von Fortpflanzungsprozessen in Laborkulturen des PolychaetenTyposyllis prolifera

Abstract: Factors controlling the timing of reproduction in laboratory cultures of the polychaete Typosyllls prolifera. Typosyllis prolifera (Krohn) from Pore~ (Yugoslavia) has been cultured for 12 successive generations. The life cycle of the species in the laboratory is described briefly. During their life individuals reproduce several times (up to 15) by stolonization which, under constant laboratory conditions (LD 16:8, 20 °C), is cyclic and takes place about every 30 days. Based on the investigations of Durchon (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 9 publications
3
31
2
Order By: Relevance
“…Following studies were focused mainly on the relationship between regeneration and sexual reproduction based on experiments of removal of the pharynx and/or proventricle, which might play a role during stolonization (Durchon, , ; Junqua, ; Okada, ; Wissocq, , ). Some of the most recent studies were those published by Franke (, ), Heacox and Schroeder (), and Franke and Pfannenstiel (). After three decades, this topic re‐emerged with a study about the role of the proventricle during the stolonization of T. antoni (Weidhase, Bleidorn et al., ).…”
Section: Syllid Regenerationmentioning
confidence: 99%
“…Following studies were focused mainly on the relationship between regeneration and sexual reproduction based on experiments of removal of the pharynx and/or proventricle, which might play a role during stolonization (Durchon, , ; Junqua, ; Okada, ; Wissocq, , ). Some of the most recent studies were those published by Franke (, ), Heacox and Schroeder (), and Franke and Pfannenstiel (). After three decades, this topic re‐emerged with a study about the role of the proventricle during the stolonization of T. antoni (Weidhase, Bleidorn et al., ).…”
Section: Syllid Regenerationmentioning
confidence: 99%
“…Warm water temperatures induce the production of gametes and hasten the time to maturity in a variety of polychaetes and other taxa, e.g . the polychaetes Bispira volutacornis , Kefersteinia cirrata , Syllis prolifera , and the bivalves Ostrea edulis and Crassostrea gigas (Orton 1920; Franke 1980; Olive & Pillai 1983; Steele & Mulcahy 1999; Nash & Keegan 2003). There is an extensive literature demonstrating faster growth rates and high survival of invertebrate larvae at warm temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Polychaetes often have endogenous cycles that are maintained for months or years in the absence of external cues, so long as conditions are adequate for survival and reproduction ( e.g . Franke 1980; Olive 1995). If gametogenesis is cued by or maintained by an endogenous rhythm in O. collaris , these animals may have continued the set cycle under laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo experiments (Franke 1980(Franke , 1983a(Franke , 1983b consisting of the removal and re-implantation of the prostomiun and proventriculus have demonstrated that reproductive control in T. prolifera is linked to lunar-rhythm secretion of a prostomial hormone (Franke 1985) (Fig. 3).…”
Section: The Stolonization Strategy Of Syllidaementioning
confidence: 98%
“…The mean date of peak stolon abondance is 13 days after a new moon (NM). Sexual development is initiated towards the end of the lunar cycle, when a prostomial hormone is secreted and proventricular activity is inhibited (after Franke 1980Franke , 1983aFranke , 1983b. FM, full moon.…”
Section: The Reproductive Cycle Of Nephtys Hombergi (Nephtyidae)mentioning
confidence: 99%